Mitigation of the biosafety risks of sars-cov-2 at bsl-3 laboratories - Mustafa Sencer Karagül; Orbay Sayı; Mevlüt Demirbaş; Fahriye Saraç; Mustafa Hasöksüz (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study is to reduce the biosafety risks of laboratory exhaust air due to SARS-CoV-2 at a biosafety level-3 laboratory used for vaccine development against COVID-19 pandemic. Materials and Methods: In this study, the infrastructure and the organisation of the containment laboratory, which aimed to be used to struggle with pandemic, was used for risk assessment. Assessment of the laboratory exhaust air procedure as a component of the heating-ventilation-air conditioning system, which is significant for high-level biosafety laboratories, was conducted through a risk assessment matrix. Results: A heating system providing exhaust air exposure to heat at 90 C° before being discharged to the outside was selected as the risk mitigation strategy after the risk analysis. The system was established as an additional biosafety barrier before the discharge of laboratory exhaust air passing through high-efficiency particulate filters. The biosafety barriers provide a safer working environment by reducing the biological risk stemming from the laboratory work. It also strengthens the existing biosafety status by building a novel and extra biosafety barrier between the laboratory and the outside environment. The residual risk was reduced to an acceptable level with the help of an additional mitigation measure regarding reassessment. Conclusion: Conducting risk assessment peculiar to practices and the facility is a necessity for the successful biosafety system at high-level biosafety laboratories. According to the risk assessment carried out in this study, creating additional risk mitigation at laboratories by the guidance of a risk-averse approach particularly during the COVID-19 pandemic might provide biosafety advantages.